2017
DOI: 10.7759/cureus.1282
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Over-Utilization of Cardiac Telemetry with Pop-Ups in an Electronic Medical Record System

Abstract: Non-invasive cardiac monitoring has well-established indications and protocols. Telemetry is often overused leading to a shortage of tele-beds and an increment of hospital expenses. In some cases, patients are kept on telemetry longer than the indicated length because providers are unaware of its ongoing use. We investigated the effect of reminder pop-ups, incorporated into an electronic medical record (EMR), on minimizing the use of telemetry. Three regional hospitals implemented an electronic pop-up reminder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
(16 reference statements)
2
9
0
Order By: Relevance
“…The intervention of introducing a hard-stop into admission orders is easily accomplished and easily measurable. Although our findings are from a single institution, other investigators have found similar results when investigating the use of prompts or ‘hardwiring’ order sets to minimise the use of telemetry not supported by the AHA guidelines 11 20…”
Section: Resultssupporting
confidence: 72%
“…The intervention of introducing a hard-stop into admission orders is easily accomplished and easily measurable. Although our findings are from a single institution, other investigators have found similar results when investigating the use of prompts or ‘hardwiring’ order sets to minimise the use of telemetry not supported by the AHA guidelines 11 20…”
Section: Resultssupporting
confidence: 72%
“…In addition, the duration of telemetry fell by 47% (before implementation of AHA guidelines=57.8±2.4 (mean±SD) hours vs. after implementation of AHA guidelines=30.9±0.9 (mean±SD) hours). Similarly, Rizvi et al focused on the notification for renewal of telemetry after 48 hours and caused a significant reduction in duration of telemetry from 3.61 to 2.7 days [12]. Our approach concentrated on residents to reduce an inappropriate use of telemetry and produced clinically meaningful results cited above.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple investigators have demonstrated a reduction in telemetry utilization by using various approaches [8,[11][12][13][14]. By hardwiring AHA guidelines into their electronic ordering system (EOS), Dressler et al observed a 43% reduction in weekly number of telemetry orders (before implementation of AHA guidelines=1032.3±32.1 [mean±SD] vs. after implementation of AHA guidelines=593.2±21.3 [mean±SD]) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Further interventions likely need to be incorporated to remind providers of the need to discontinue telemetry at the earliest appropriate opportunity as clinically indicated. A study by Rizvi et al showed that incorporating pop-ups in the electronic medical system for discontinuing telemetry reduced overuse of telemetry by 37% [8]. Such an intervention or the use of expiration dates with initial order of telemetry, which currently does not exist in our hospital, may be helpful in stopping telemetry when no longer indicated.…”
Section: Discussionmentioning
confidence: 99%